Researching Cognitive Processes of Translation - Li, Defeng; Lei, Victoria Lai Cheng; He, Yuanjian (New Frontiers in Translation Studies, 2019)
This edited volume covers an array of the most relevant topics in translation cognition, taking different approaches and using different research tools. It explores theoretical and methodological issues using case studies and examining their practical and pedagogical implications. It is a valuable resource for translation studies scholars, graduate students and those interested in translation and translation training, enabling them to conceptualize translation cognition, in order to enhance their research methods and designs, manage innovations in their translation training or simply understand their own translation behaviours.